Rethinking ‘cultural activities’: An examination of how teachers utilised student voice as a pedagogical tool in multicultural schools - Szelei, Nikolett (2022)
This article explores the activities teachers developed in a school cluster in Portugal in order to address cultural diversity, and particularly, how students' voices were used as pedagogical tools. Findings show unsettled rather than unified strategies, building on cultural artefacts, universal/individualised topics, and tackling stereotyping, discrimination and racism. However, student voice as a pedagogical tool seemed to be missing, possibly leaving pupils misrepresented and disengaged. It is suggested that the element between teachers’ good intentions and contradictory practices in pedagogies for cultural diversity might be the absence of student voice work in the decision-making process on representation, identification and participation.